Ambiguity in Literal and Non-literal Meaning: A Pragmatic Linguistic Analysis - Ariel Jonivedi Silalahi; Bernieke Anggita Ristia Damanik (Yayasan Bayt Shufiya Nusantara, 2025)
Ambiguity in language often arises when meaning depends on contextual interpretation, particularly in the use of non-literal expressions such as idioms, metaphors, irony, and sarcasm. This phenomenon can hinder communication, especially among non-native speakers who may lack sufficient linguistic or cultural background to interpret intended meanings accurately. This study aims to analyze how pragmatic ambiguity operates and the role of context in resolving it. Using a literature review method, the study synthesizes findings from linguistic research published in the last decade. The results indicate that pragmatic ambiguity frequently occurs due to limited contextual cues, tone, and shared background knowledge. Three types of context linguistic, situational, and cultural were found to be crucial in disambiguation processes. While ambiguity may cause misunderstanding, it can also be used strategically to convey nuanced meaning, humor, and indirectness. The study concludes that strengthening pragmatic competence is essential for improving communicative effectiveness.